FAKTOR YANG MEMPENGARUHI KEPATUHAN KARYAWAN DALAM MELAKSANAKAN PROTOKOL KESEHATAN UNTUK MENCEGAH PENULARAN COVID-19 DI PT KBAS KABUPATEN KETAPANG - Ratri, Yoka Risma Mustika; Kusumawati, Yuli; Kusumaningrum, Tanjung Anitasari Indah (VISIKES: Jurnal Kesehatan Masyarakat, 2023)
ABSTRACT Background: The Covid-19 virus is still a health problem to this day. The virus that continues to mutate makes various new variants of the Covid-19 virus appear. From these conditions, it indicates that the pandemic is not over. The best thing that can be done is to continue to implement health protocols. Employees or employees are workers who are very vulnerable to being infected with Covid-19. Compliance in implementing health protocols is the main key to break the chain of spread of the Covid 19 virusMethods: This type of research is . quantitative with a cross-sectional approach. The research population is employees at PT KBAS, a total of 223 people. The research sample was 142 respondents using the Stratified Random Sampling technique. The instrument used in the form of a questionnaire, data analysis using the Chi square test.Results: Factors related to employee compliance behavior in implementing health protocols in the workplace are perceived vulnerability (p-value = <0,001), perceived seriousness (p-value = 0,<001), benefit cues (p-value = 0,001), and self-confidence ( p-value = 0,018). Meanwhile, perceived barriers (p-value = 0,488) and cues to act (p-value = 0,277) were not related to employee compliance behavior in implementing health protocols in the workplace. Keywords: Covid 19, Employees, Emplience